FABRICATION AND CHARACTERIZATION OF CHITOSAN NANOPARTICLES FOR EFFICIENT DELIVERY OF KAEMPFEROL IN BREAST AND CERVICAL CANCER TREATMENT - SARANYA MV; SUDHA T (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The goal of the present study was to use factorial design to prepare and optimize chitosan nanoparticles loaded with kaempferol for targeted drug delivery. A systematic investigation was conducted into the effects of major preparation variables, polymer amount, sodium tripolyphosphate (TPP) quantity, and stirring speed on drug content, encapsulation efficiency, and cumulative drug release (CDR). Methods: Using TPP as a cross-linker and chitosan as a biodegradable polymer, kaempferol-loaded chitosan nanoparticles were created through an altered ionic gelation process. The formulation parameters were optimized using a factorial design. A number of nanoparticle characteristics, such as CDR, encapsulation effectiveness, and particle size, were described. A scanning electron microscope was used to investigate the prepared nanoparticles morphology. In addition, the MTT assay was used to evaluate cytotoxicity on the MCF-7 and HeLa human cancer cell line for breast and cervical cancer. Results: Particle size of 112.5 nm, drug content of 96.63±0.531%, encapsulation efficiency of 89.45±0.311%, cumulative drug release (CDR) of 94.63±0.03%, zeta potential of −24.2 mV, and polydispersity index of 0.192 are all characteristics of the optimal formulation. The nanoparticles’ spherical shape was revealed by the scanning electron microscope results. Studies on in vitro cytotoxicity revealed that the chitosan nanoparticles loaded with kaempferol demonstrated strong anticancer properties, with IC50 values of 68.00 μg/mL for HeLa cell lines and 55.00 μg/mL for MCF-7. The significant p-values were found to be 0.0480, 0.0191, and 0.0372 for all responses. The formulations were included based on chitosan (≥85% deacetylation), kaempferol (≥98% purity), and nanoparticle formulations with size <200 nm, PDI ≤0.3, drug content ≥80%, and encapsulation efficiency ≥70%. Only actively growing, uncontaminated HeLa, and MCF-7 cells (≥95% viability, passages 3–10) were used for cytotoxicity studies. Conclusion: Therefore, it is possible that the newly discovered nanoparticles for the treatment of breast and cervical cancer represent a ground-breaking approach. These findings significantly support the possibility of using these nanoparticles as a therapeutic treatment for breast and cervical cancer patients undergoing or following resection of malignant lesions.